PENGARUH FAKTOR PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MATA UANG KRIPTO PADA GENERASI SANDWICH DI JAKARTA - Oktafalia Marisa Muzammil; Stefina Mariam (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
In general, the sandwich generation is a term for certain people who are generally of mature or productive age who have multiple roles. The dual role of the sandwich generation is their role in being responsible for the family, in this case the child is also responsible for the parents. The burden of the sandwich generation has become not easy. The challenge is how to meet the needs of the two generations they bear. If the needs and costs can no longer be reduced then another step that can be taken is to increase income. Investment can be the answer to the challenges faced. This generation is also faced with a variety of investment choices. One of the current investment instruments is crypto currency. Crypto currency is digital or virtual currency that is secured by cryptography, which makes it nearly impossible to counterfeit or duplicate. A distinctive feature of crypto currencies is that they are generally not issued by a central authority, making them theoretically immune to government interference or manipulation. Crypto itself "refers to the various encryption algorithms and cryptographic techniques that protect these entries, such as elliptic curve encryption, public-private key pairs, and hashing functions. Nevertheless, the choice of crypto currency investment must be careful. This study wants to know the extent to which consumer behavior from the sandwich generation will affect crypto currency purchasing decisions. Consumer behavior factors that will be discussed in this study are personal, psychological, social, and cultural factors. This research will use multiple regression analysis to obtain conclusions that support the developed hypothesis.